Penerapan Metode Profile Matching dalam Sistem Penunjang Keputusan untuk Menentukan Kelayakan Siswa PAUD Naik ke Jenjang Taman Kanak-kanak (TK) Berbasis Website di Pos PAUD Anggrek RW 09 - Fathan Khaiza Septiansyah; Fadly Ariadi (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Advances in information technology have encouraged educational institutions to improve the effectiveness of data-based evaluation and decision-making processes. POS PAUD Anggrek RW 09 still uses manual and subjective assessment methods to determine student eligibility for advancement to kindergarten (TK), resulting in an evaluation process that is inaccurate, unstructured, and time-consuming. This study aims to develop a website-based Decision Support System (DSS) using the Profile Matching method to help educators conduct objective, systematic, and measurable assessments. The Profile Matching method is used because it is able to compare students' ability profiles with ideal profiles based on child development criteria, such as motor skills, letter recognition, social interaction, vocabulary, counting, and independence. This system performs automatic calculations, starting from the GAP value, Core Factor and Secondary Factor weighting, to producing a final score and recommendations on student eligibility status. This study used observation, interviews, and literature review methods in data collection, and applied a system development method through the stages of analysis, design, implementation, and testing. The results showed that the decision support system that was developed was able to produce accurate and objective calculations to determine the eligibility of students to advance to kindergarten. The system also simplifies the data management process, improves evaluation efficiency, and provides transparency in the decision-making process at POS PAUD Anggrek RW 09. Thus, this website-based DSS can be an important tool in supporting the improvement of early childhood education quality.